THE NARRATIVE OF CHARACTER EDUCATION VALUES IN DATU DIYANG FOLKTALE - Ali, Ahmad Jum'a Khatib Nur; Riady, Yasir; Hidayat, Arif (Universitas Gunadarma, 2024)
The internalization of good character education values is an inevitability in nation-building. Folktales are one of the mediums for teaching character education values. Therefore, this study aims to reveal the character education values and how these values are narrated in folktales. The object of this study is the folktale Kisah Datu Diyang from South Kalimantan. The method used is descriptive qualitative with documentation techniques as the data collection technique. The concept of character education values is based on Lickona's theory. The results show that the object of the study contains four values: caring for others, honesty, responsibility, and humility. The study also shows that the narration of values does not use monologue and is more dominated by the narrator followed by dialogue. The results also indicate that there are two parts of the narrative pattern, namely before and after Diyang becomes a midwife with the narrative pattern D1FHJIjMNQ.